Pengaruh Brand Attachment dan Perceived Quality terhadap Keputusan Pembelian - Wisnu, I Gusti Putu Agus (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
This study aims to determine the effect of brand attachment and Perceived Quality on the Purchase Decision of Oppo Brand Mobile Phones (Case Study at Counter Tunjung Bali Cellular Tabanan) partially and simultaneously. In this study, the data collection methods used were observation, interviews, questionnaires, and literature study. The population in this study are people who buy Oppo brand mobile phones at the Tunjung Bali Cellular Tabanan Counter. The sample used in this study was 120 respondents, using the Cochran formula. The data analysis techniques used in this study are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Correlation Coefficient Analysis Test, Coefficient of Determination Test, t Test and F Test. From the results of the study, it was found that: Brand Attachment and Perceived Quality partially and simultaneously influence the Purchase Decision of the Oppo brand cellphone at the Tunjung Bali Celluler Counter Tabanan. The regression equation obtained is Y = 7,430 + 0,411 X1 + 0,431 X2 + e. The magnitude of the influence of brand attachment and perceived quality on purchasing decisions is 77.6%, while the remaining 22.4% there are other variables that influence purchasing decisions, such as service quality, price, and promotion.